TEKNIK KOMUNIKASI TERAPEUTIK DALAM MENANGANI PERILAKU FANATISME PASIEN DI POLI UMUM KLINIK BUMI SEHAT UBUD GIANYAR BALI - Redi Panuju (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2019)
The socio-cultural development of the community is a sign that the community in a certain area has experienced a change in the process of thinking. Changes in lifestyle caused by the inclusion of external culture will influence the pattern of thinking and perspective on health, because culture and health have a significant correlation. It is important to straighten out the beliefs or culture that the relationship adheres to with health, so that there are no mistakes in people's thinking patterns or perspectives that can adversely affect their health. For this reason, a therapeutic communication technique is needed by health workers. Based on the theory of S.O.R (Stimulus-Organism-Response) and four basic techniques of therapeutic communication; Listening techniques, questioning techniques, concluding techniques and techniques change the perspective as testers in data analysis. The conclusion from the results of this study shows that the technique used by health workers at the Bumi Sehat clinic in dealing with patient fanaticism is to combine the use of verbal and non-verbal language actively and effectively in each of the basic techniques of applied therapeutic communication.